Multifunctional composite hydrophobic membrane and preparation method thereof
By modifying nanosilica and hydroxyl multi-walled carbon nanotubes and combining them with polyvinylidene fluoride-hexafluoropropylene copolymer, multifunctional composite hydrophobic membranes are prepared using electrospinning technology, which solves the problems of poor controllability and general stability in the preparation process of existing hydrophobic membranes, and achieves efficient hydrophobic properties and chemical stability.
Patent Information
- Application Number
- CN202411866028.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing hydrophobic membranes have poor controllability and average stability during the preparation process, and the surface of the membrane is easily wet, which affects its application effect.
By modifying nanosilica and hydroxyl multi-walled carbon nanotubes, alkenyl and ATRP initiation points are introduced to form a modified composite material combined with polyvinylidene fluoride-hexafluoropropylene copolymer, and a multifunctional composite hydrophobic film is prepared by electrospinning technology.
The stability and hydrophobic properties of the hydrophobic membrane are improved, the contact angle on the surface of the membrane is increased, the anti-fouling ability and chemical stability are enhanced, and the mechanical properties and toughness of the membrane are improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrophobic membrane materials, in particular to a multifunctional composite hydrophobic membrane and a preparation method thereof. Background Art
[0002] Hydrophobic membrane is a special membrane material with hydrophobic surface, which repels water molecules but allows gas or other liquids to pass through. The basic principle of hydrophobic membrane is based on the low surface energy characteristics of its surface, which makes water molecules form a large contact angle on the membrane surface, making it difficult to wet and penetrate. This characteristic makes hydrophobic membranes can be used to treat industrial wastewater, purify air, desalinate seawater, etc., and has a wide range of applications in liquid-gas separation, water treatment, air purification and other fields.
[0003] The preparation materials of hydrophobic membrane mainly include materials such as polypropylene, polyvinylidene fluoride, polyethylene and polytetrafluoroethylene, and the traditional membrane making process includes non-solvent induced phase separation, thermally induced phase separation and melt-stretching. Chinese patent application CN101531764A discloses a super-hydrophobic polypropylene film and a preparation method thereof, wherein a polypropylene film is prepared by a method of adding acetone to a polypropylene solution, and a microphase separation is produced by inducing a polypropylene solution with acetone to form an irregular structure, thereby obtaining a super-hydrophobic surface, and the surface of the prepared polypropylene film is a network-like bird's nest structure of porous crystals, and the hydrophobic performance is good, but the controllability of its preparation process is poor and the stability is general. The membrane prepared by the electrostatic spinning method has better controllability. In recent years, the preparation of membrane materials by electrostatic spinning technology has received widespread attention. Chinese patent application CN103263856A discloses a method for preparing an electrospun hydrophobic nanofiber porous membrane for membrane distillation, wherein a hydrophobic functional polymer material is dissolved in a solvent to obtain a polymer spinning solution, electrospinning is performed to obtain a hydrophobic nanofiber porous membrane, and then heat treatment is performed to obtain an electrospun hydrophobic nanofiber porous membrane for membrane distillation. However, the water contact angle of the porous membrane is only 120-135°, and there is still a disadvantage that the membrane surface is easily wetted. Chinese patent application CN105413488A discloses a method for preparing a super-hydrophobic membrane, which comprises dissolving a hydrophobic organic polymer material and nanoparticles in an organic solvent, stirring and standing to prepare an electrospinning solution, electrospinning to obtain a nanofiber membrane, and heat-treating the nanofiber membrane; covering the surface of the nanofiber membrane with TiO2, and then subjecting the membrane to heat treatment, water bath heating, rinsing and ultraviolet irradiation treatment; preparing a silane solution, covering the surface of the nanofiber membrane coated with TiO2 with the silane solution, and then subjecting the membrane to heat treatment, rinsing and drying to obtain a super-hydrophobic membrane, which has the characteristics of super-hydrophobicity, effectively improves the membrane's anti-wetting property, and prolongs the membrane's service life, but the nanoparticles are easy to agglomerate, and their presence in the nanofiber membrane will destroy the structure of the nanofiber membrane and reduce the porosity. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In order to solve the above technical problems, the present invention provides a multifunctional composite hydrophobic membrane and a preparation method thereof, and provides a hydrophobic membrane with good stability and excellent hydrophobicity.
[0006] (II) Technical solution
[0007] In order to achieve the above object, the present invention discloses a method for preparing a multifunctional composite hydrophobic membrane, comprising the following steps:
[0008] Step 1, ultrasonically disperse nano-silica into an ethanol solution, and after uniform dispersion, add γ-methacryloxypropyltrimethoxysilane, adjust the pH to 4 with a hydrochloric acid solution, stir and mix, react, and after the reaction is completed, filter, wash with anhydrous ethanol and deionized water respectively, and dry at 80° C. for 12 hours to obtain olefinated silica;
[0009] Step 2: Ultrasonic dispersion of hydroxyl multi-walled carbon nanotubes in tetrahydrofuran, after uniform dispersion, adding triethylamine, adding 2-bromoisobutyl bromide in a nitrogen atmosphere, stirring and mixing, reacting, centrifuging after the reaction, washing with methanol, and drying at 60° C. for 12 h to obtain modified carbon nanotubes;
[0010] Step 3: uniformly mix the modified carbon nanotubes, cuprous chloride, perfluorooctyl ethyl acrylate, olefinated silica, and tetrahydrofuran, add 1,1,4,7,10,10-hexamethyltriethylenetetramine in a nitrogen atmosphere to react, centrifuge after the reaction, wash with tetrahydrofuran, and vacuum dry at 60° C. for 12 h to obtain a modified composite material;
[0011] Step 4: Evenly mix N,N-dimethylformamide and acetone, add polyvinylidene fluoride-hexafluoropropylene copolymer and mix evenly, add modified composite material, stir and mix for 2-5 hours, let stand to degas, and obtain spinning solution, add the spinning solution to the spinning machine for electrostatic spinning to form fibers, and deposit them on the polyester mesh base to obtain a multifunctional composite hydrophobic membrane.
[0012] Preferably, in the step 1, the mass ratio of the nano-silica, the ethanol solution and γ-methacryloxypropyltrimethoxysilane is 100:1800-2100:18-35.
[0013] Preferably, the ethanol solution in step 1 consists of anhydrous ethanol and deionized water in a volume ratio of 1:1.
[0014] Preferably, the reaction temperature in step 1 is 65-75° C., and the reaction time is 4-6 h.
[0015] Preferably, in the step 2, the mass ratio of the hydroxyl multi-walled carbon nanotubes, tetrahydrofuran, triethylamine and 2-bromoisobutyl bromide is 100:4500-5000:152-180:135-175.
[0016] Preferably, during the reaction in step 2, the reaction is first carried out at 0° C. for 4 hours, and then at 25° C. for 36-48 hours.
[0017] Preferably, in the step three, the mass ratio of the modified carbon nanotubes, cuprous chloride, perfluorooctyl ethyl acrylate, olefinated silica, tetrahydrofuran, and 1,1,4,7,10,10-hexamethyltriethylenetetramine is 100:55-65:680-720:25-42:6500-8000:300-350.
[0018] Preferably, the reaction temperature in step 3 is 65-75° C., and the reaction time is 48-54 h.
[0019] Preferably, in step 4, the mass ratio of the N,N-dimethylformamide, acetone, polyvinylidene fluoride-hexafluoropropylene copolymer, and modified composite material is 360-420:90-105:100:5-18.
[0020] Preferably, during the electrospinning process in step 4, the distance between the needle and the receiving roller is 12-18 cm, the spinning voltage is 15-18 kV, the spinning time is 12-18 h, and the propulsion speed of the spinning solution is 1.2-1.5 mL / h.
[0021] A multifunctional composite hydrophobic membrane prepared by adopting the method for preparing the multifunctional composite hydrophobic membrane.
[0022] 3. Beneficial technical effects
[0023] In the present invention, γ-methacryloxypropyltrimethoxysilane is used to modify nano silicon dioxide, alkenyl groups are introduced on the surface of nano silicon dioxide to obtain alkenyl silicon dioxide, 2-bromoisobutyl bromide is used to modify hydroxyl multi-walled carbon nanotubes, ATRP initiation points are introduced on the surface of carbon nanotubes to obtain modified carbon nanotubes. The bromine initiation groups on the surface of the modified carbon nanotubes initiate polymerization of perfluorooctylethyl acrylate and alkenyl silicon dioxide to obtain a modified composite material, polyvinylidene fluoride-hexafluoropropylene copolymer is used as a membrane material, the modified composite material is added, and fibers are formed by electrostatic spinning, which are deposited on a polyester mesh substrate to obtain a multifunctional composite hydrophobic membrane.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) In the present invention, nano-silica and hydroxyl multi-walled carbon nanotubes are modified, which effectively improves the dispersibility of the two, and can be evenly dispersed in the matrix, effectively avoiding agglomeration. Polyvinylidene fluoride-hexafluoropropylene copolymer is used as a substrate, which has good mechanical strength and toughness. The synergistic effect of modified carbon nanotubes and olefinic silica with polyvinylidene fluoride-hexafluoropropylene copolymer, the introduction of inorganic-organic nano-hybrid materials can achieve microscopic multidimensional roughness of the membrane surface, and the low surface energy polymer can effectively reduce the surface energy of the membrane material. The membrane surface has a lower surface energy and a rougher structure, which enhances the hydrophobicity and increases the contact angle. The fluorine atoms in the structure of perfluorooctyl ethyl acrylate have a low surface energy, which can significantly reduce the surface energy of the membrane, and have excellent hydrophobicity and oleophobicity, further improving the hydrophobicity of the membrane material. Perfluorooctyl ethyl acrylate has good chemical stability and can withstand the erosion of various chemical substances. It synergizes with inorganic materials to enhance the chemical stability of the membrane, so that it can maintain stable performance under various environments.
[0026] (2) The fiber structure prepared by electrospinning technology in the present invention is conducive to forming a super-hydrophobic surface. In the hydrophobic membrane, the fluorocarbon chain of perfluorooctyl ethyl acrylate tends to migrate to the membrane surface and arrange neatly, so that the modified filler forms a micro-nano structure on the membrane surface, increasing the roughness of the membrane surface and further enhancing the hydrophobic properties of the membrane. Nano-silicon dioxide, as an inorganic nanoparticle, can be filled in the membrane material to form an inorganic-organic composite structure to improve the mechanical strength of the membrane. Carbon nanotubes can form a network structure in the membrane. This structure is conducive to enhancing the mechanical properties and toughness of the membrane. The two work synergistically to enhance the chemical stability of the membrane material and protect the membrane material from corrosion by chemical substances. At the same time, the hydrophobic membrane has excellent anti-fouling ability, reduces the adsorption and deposition of pollutants on the membrane surface, and maintains the patency of the membrane pores. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0028] Example 1
[0029] A method for preparing a multifunctional composite hydrophobic membrane comprises the following steps:
[0030] (1) Ultrasonic dispersion of nano-silica in an ethanol solution, wherein the ethanol solution is composed of anhydrous ethanol and deionized water in a volume ratio of 1:1, and after uniform dispersion, γ-methacryloxypropyltrimethoxysilane is added, wherein the mass ratio of nano-silica, ethanol solution, and γ-methacryloxypropyltrimethoxysilane is 100:1800:18, and the pH value is adjusted to 4 with a hydrochloric acid solution, and the mixture is stirred and reacted at a temperature of 65°C and a reaction time of 6 hours. After the reaction is completed, the mixture is filtered, washed with anhydrous ethanol and deionized water respectively, and dried at 80°C for 12 hours to obtain olefinated silica;
[0031] (2) Ultrasonic dispersion of hydroxyl multi-walled carbon nanotubes in tetrahydrofuran, after uniform dispersion, adding triethylamine, and in a nitrogen atmosphere, adding 2-bromoisobutyl bromide, wherein the mass ratio of hydroxyl multi-walled carbon nanotubes, tetrahydrofuran, triethylamine, and 2-bromoisobutyl bromide is 100:4500:152:135, stirring and mixing, reacting, first at 0°C for 4h, then at 25°C for 36h, after the reaction is completed, centrifuging, washing with methanol, and drying at 60°C for 12h to obtain modified carbon nanotubes;
[0032] (3) The modified carbon nanotubes, cuprous chloride, perfluorooctyl ethyl acrylate, olefinic silica, and tetrahydrofuran were uniformly mixed, and 1,1,4,7,10,10-hexamethyltriethylenetetramine was added in a nitrogen atmosphere, wherein the mass ratio of the modified carbon nanotubes, cuprous chloride, perfluorooctyl ethyl acrylate, olefinic silica, tetrahydrofuran, and 1,1,4,7,10,10-hexamethyltriethylenetetramine was 100:55:680:25:6500:300, and a reaction was carried out at a temperature of 65°C for a reaction time of 54 hours. After the reaction was completed, the mixture was centrifuged, washed with tetrahydrofuran, and vacuum dried at 60°C for 12 hours to obtain a modified composite material;
[0033] (4) N,N-dimethylformamide and acetone were mixed evenly, polyvinylidene fluoride-hexafluoropropylene copolymer was added and mixed evenly, and the modified composite material was added, wherein the mass ratio of N,N-dimethylformamide, acetone, polyvinylidene fluoride-hexafluoropropylene copolymer and modified composite material was 360:90:100:5. After stirring and mixing for 2 hours, the mixture was allowed to stand for degassing to obtain a spinning solution, and the spinning solution was added to a spinning machine for electrospinning to form fibers, which were deposited on a polyester mesh substrate. During the electrospinning process, the distance between the needle and the receiving roller was 12 cm, the spinning voltage was 15 kV, the spinning time was 18 h, and the propulsion speed of the spinning solution was 1.2 mL / h to obtain a multifunctional composite hydrophobic membrane.
[0034] Example 2
[0035] A method for preparing a multifunctional composite hydrophobic membrane comprises the following steps:
[0036] (1) Ultrasonic dispersion of nano-silica in an ethanol solution, wherein the ethanol solution is composed of anhydrous ethanol and deionized water in a volume ratio of 1:1, and after uniform dispersion, γ-methacryloxypropyltrimethoxysilane is added, wherein the mass ratio of nano-silica, ethanol solution, and γ-methacryloxypropyltrimethoxysilane is 100:1900:25, and the pH value is adjusted to 4 with a hydrochloric acid solution, and the mixture is stirred and reacted at a temperature of 70°C and a reaction time of 5 hours. After the reaction is completed, the mixture is filtered, washed with anhydrous ethanol and deionized water respectively, and dried at 80°C for 12 hours to obtain olefinated silica;
[0037] (2) Ultrasonic dispersion of hydroxyl multi-walled carbon nanotubes in tetrahydrofuran, after uniform dispersion, adding triethylamine, and in a nitrogen atmosphere, adding 2-bromoisobutyl bromide, wherein the mass ratio of hydroxyl multi-walled carbon nanotubes, tetrahydrofuran, triethylamine, and 2-bromoisobutyl bromide is 100:4800:162:150, stirring and mixing, reacting, first at 0°C for 4h, then at 25°C for 42h, after the reaction is completed, centrifuging, washing with methanol, and drying at 60°C for 12h to obtain modified carbon nanotubes;
[0038] (3) The modified carbon nanotubes, cuprous chloride, perfluorooctyl ethyl acrylate, olefinic silica, and tetrahydrofuran were mixed evenly, and 1,1,4,7,10,10-hexamethyltriethylenetetramine was added in a nitrogen atmosphere, wherein the mass ratio of the modified carbon nanotubes, cuprous chloride, perfluorooctyl ethyl acrylate, olefinic silica, tetrahydrofuran, and 1,1,4,7,10,10-hexamethyltriethylenetetramine was 100:58:705:35:7500:320, and a reaction was carried out at a temperature of 70°C for a reaction time of 52 hours. After the reaction was completed, the mixture was centrifuged, washed with tetrahydrofuran, and vacuum dried at 60°C for 12 hours to obtain a modified composite material;
[0039] (4) N,N-dimethylformamide and acetone were mixed evenly, polyvinylidene fluoride-hexafluoropropylene copolymer was added and mixed evenly, and the modified composite material was added, wherein the mass ratio of N,N-dimethylformamide, acetone, polyvinylidene fluoride-hexafluoropropylene copolymer and modified composite material was 380:95:100:10. After stirring and mixing for 3 hours, the mixture was allowed to stand for degassing to obtain a spinning solution, and the spinning solution was added to a spinning machine for electrospinning to form fibers, which were deposited on a polyester mesh substrate. During the electrospinning process, the distance between the needle and the receiving roller was 14 cm, the spinning voltage was 16 kV, the spinning time was 14 h, and the propulsion speed of the spinning solution was 1.4 mL / h to obtain a multifunctional composite hydrophobic membrane.
[0040] Example 3
[0041] A method for preparing a multifunctional composite hydrophobic membrane comprises the following steps:
[0042] (1) Ultrasonic dispersion of nano-silica in an ethanol solution, wherein the ethanol solution is composed of anhydrous ethanol and deionized water in a volume ratio of 1:1, and after uniform dispersion, γ-methacryloxypropyltrimethoxysilane is added, wherein the mass ratio of nano-silica, ethanol solution, and γ-methacryloxypropyltrimethoxysilane is 100:1900:25, and the pH value is adjusted to 4 with a hydrochloric acid solution, and the mixture is stirred and reacted at a temperature of 70°C and a reaction time of 5 hours. After the reaction is completed, the mixture is filtered, washed with anhydrous ethanol and deionized water respectively, and dried at 80°C for 12 hours to obtain olefinated silica;
[0043] (2) Ultrasonic dispersion of hydroxyl multi-walled carbon nanotubes in tetrahydrofuran, after uniform dispersion, adding triethylamine, and in a nitrogen atmosphere, adding 2-bromoisobutyl bromide, wherein the mass ratio of hydroxyl multi-walled carbon nanotubes, tetrahydrofuran, triethylamine, and 2-bromoisobutyl bromide is 100:4800:162:150, stirring and mixing, reacting, first at 0°C for 4h, then at 25°C for 42h, after the reaction is completed, centrifuging, washing with methanol, and drying at 60°C for 12h to obtain modified carbon nanotubes;
[0044] (3) The modified carbon nanotubes, cuprous chloride, perfluorooctyl ethyl acrylate, olefinic silica, and tetrahydrofuran were mixed evenly, and 1,1,4,7,10,10-hexamethyltriethylenetetramine was added in a nitrogen atmosphere, wherein the mass ratio of the modified carbon nanotubes, cuprous chloride, perfluorooctyl ethyl acrylate, olefinic silica, tetrahydrofuran, and 1,1,4,7,10,10-hexamethyltriethylenetetramine was 100:58:705:35:7500:320, and a reaction was carried out at a temperature of 70°C for a reaction time of 52 hours. After the reaction was completed, the mixture was centrifuged, washed with tetrahydrofuran, and vacuum dried at 60°C for 12 hours to obtain a modified composite material;
[0045] (4) N,N-dimethylformamide and acetone were mixed evenly, polyvinylidene fluoride-hexafluoropropylene copolymer was added and mixed evenly, and the modified composite material was added, wherein the mass ratio of N,N-dimethylformamide, acetone, polyvinylidene fluoride-hexafluoropropylene copolymer and modified composite material was 400:100:100:15. After stirring and mixing for 4 hours, the mixture was allowed to stand for degassing to obtain a spinning solution, and the spinning solution was added to a spinning machine for electrospinning to form fibers, which were deposited on a polyester mesh substrate. During the electrospinning process, the distance between the needle and the receiving roller was 14 cm, the spinning voltage was 17 kV, the spinning time was 16 h, and the propulsion speed of the spinning solution was 1.4 mL / h to obtain a multifunctional composite hydrophobic membrane.
[0046] Example 4
[0047] A method for preparing a multifunctional composite hydrophobic membrane comprises the following steps:
[0048] (1) Ultrasonic dispersion of nano-silica in an ethanol solution, wherein the ethanol solution is composed of anhydrous ethanol and deionized water in a volume ratio of 1:1, and after uniform dispersion, γ-methacryloxypropyltrimethoxysilane is added, wherein the mass ratio of nano-silica, ethanol solution, and γ-methacryloxypropyltrimethoxysilane is 100:2100:35, and the pH value is adjusted to 4 with a hydrochloric acid solution, and the mixture is stirred and reacted at a temperature of 75°C and a reaction time of 4 hours. After the reaction is completed, the mixture is filtered, washed with anhydrous ethanol and deionized water respectively, and dried at 80°C for 12 hours to obtain olefinated silica;
[0049] (2) Ultrasonic dispersion of hydroxyl multi-walled carbon nanotubes in tetrahydrofuran, after uniform dispersion, adding triethylamine, and in a nitrogen atmosphere, adding 2-bromoisobutyl bromide, wherein the mass ratio of hydroxyl multi-walled carbon nanotubes, tetrahydrofuran, triethylamine, and 2-bromoisobutyl bromide is 100:5000:180:175, stirring and mixing, reacting, first reacting at 0°C for 4h, and then reacting at 25°C for 48h. After the reaction is completed, centrifugation is performed, washing with methanol, and drying at 60°C for 12h to obtain modified carbon nanotubes;
[0050] (3) The modified carbon nanotubes, cuprous chloride, perfluorooctyl ethyl acrylate, olefinic silica, and tetrahydrofuran were mixed uniformly, and 1,1,4,7,10,10-hexamethyltriethylenetetramine was added in a nitrogen atmosphere, wherein the mass ratio of the modified carbon nanotubes, cuprous chloride, perfluorooctyl ethyl acrylate, olefinic silica, tetrahydrofuran, and 1,1,4,7,10,10-hexamethyltriethylenetetramine was 100:65:720:42:8000:350, and a reaction was carried out at a temperature of 75°C for 48 hours. After the reaction was completed, the mixture was centrifuged, washed with tetrahydrofuran, and vacuum dried at 60°C for 12 hours to obtain a modified composite material;
[0051] (4) N,N-dimethylformamide and acetone were mixed evenly, polyvinylidene fluoride-hexafluoropropylene copolymer was added and mixed evenly, and the modified composite material was added, wherein the mass ratio of N,N-dimethylformamide, acetone, polyvinylidene fluoride-hexafluoropropylene copolymer and modified composite material was 420:105:100:18. After stirring and mixing for 5 hours, the mixture was allowed to stand for degassing to obtain a spinning solution, and the spinning solution was added to a spinning machine for electrospinning to form fibers, which were deposited on a polyester mesh substrate. During the electrospinning process, the distance between the needle and the receiving roller was 18 cm, the spinning voltage was 18 kV, the spinning time was 12 h, and the propulsion speed of the spinning solution was 1.5 mL / h to obtain a multifunctional composite hydrophobic membrane.
[0052] Comparative Example 1
[0053] A method for preparing a composite hydrophobic membrane comprises the following steps:
[0054] (1) Ultrasonic dispersion of nano-silica in an ethanol solution, wherein the ethanol solution is composed of anhydrous ethanol and deionized water in a volume ratio of 1:1, and after uniform dispersion, γ-methacryloxypropyltrimethoxysilane is added, wherein the mass ratio of nano-silica, ethanol solution, and γ-methacryloxypropyltrimethoxysilane is 100:1900:25, and the pH value is adjusted to 4 with a hydrochloric acid solution, and the mixture is stirred and reacted at a temperature of 70°C and a reaction time of 5 hours. After the reaction is completed, the mixture is filtered, washed with anhydrous ethanol and deionized water respectively, and dried at 80°C for 12 hours to obtain olefinated silica;
[0055] (2) Ultrasonic dispersion of hydroxyl multi-walled carbon nanotubes in tetrahydrofuran, after uniform dispersion, adding triethylamine, and in a nitrogen atmosphere, adding 2-bromoisobutyl bromide, wherein the mass ratio of hydroxyl multi-walled carbon nanotubes, tetrahydrofuran, triethylamine, and 2-bromoisobutyl bromide is 100:4800:162:150, stirring and mixing, reacting, first at 0°C for 4h, then at 25°C for 42h, after the reaction is completed, centrifuging, washing with methanol, and drying at 60°C for 12h to obtain modified carbon nanotubes;
[0056] (3) N,N-dimethylformamide and acetone were mixed evenly, polyvinylidene fluoride-hexafluoropropylene copolymer was added and mixed evenly, and modified carbon nanotubes, perfluorooctyl ethyl acrylate and olefinic silica were added, wherein the mass ratio of N,N-dimethylformamide, acetone, polyvinylidene fluoride-hexafluoropropylene copolymer, modified carbon nanotubes, perfluorooctyl ethyl acrylate and olefinic silica was 400:100:100:1.8:12.5:0.7. After stirring and mixing for 4 hours, the mixture was allowed to stand for degassing to obtain a spinning solution, and the spinning solution was added to a spinning machine for electrospinning to form fibers, which were deposited on a polyester mesh substrate. During the electrospinning process, the distance between the needle and the receiving roller was 14 cm, the spinning voltage was 17 kV, the spinning time was 16 h, and the propulsion speed of the spinning solution was 1.4 mL / h to obtain a composite hydrophobic membrane.
[0057] Comparative Example 2
[0058] A method for preparing a composite hydrophobic membrane comprises the following steps:
[0059] (1) Ultrasonic dispersion of nano-silica in an ethanol solution, wherein the ethanol solution is composed of anhydrous ethanol and deionized water in a volume ratio of 1:1, and after uniform dispersion, γ-methacryloxypropyltrimethoxysilane is added, wherein the mass ratio of nano-silica, ethanol solution, and γ-methacryloxypropyltrimethoxysilane is 100:1900:25, and the pH value is adjusted to 4 with a hydrochloric acid solution, and the mixture is stirred and reacted at a temperature of 70°C and a reaction time of 5 hours. After the reaction is completed, the mixture is filtered, washed with anhydrous ethanol and deionized water respectively, and dried at 80°C for 12 hours to obtain olefinated silica;
[0060] (2) Ultrasonic dispersion of hydroxyl multi-walled carbon nanotubes in tetrahydrofuran, after uniform dispersion, adding triethylamine, and in a nitrogen atmosphere, adding 2-bromoisobutyl bromide, wherein the mass ratio of hydroxyl multi-walled carbon nanotubes, tetrahydrofuran, triethylamine, and 2-bromoisobutyl bromide is 100:4800:162:150, stirring and mixing, reacting, first at 0°C for 4h, then at 25°C for 42h, after the reaction is completed, centrifuging, washing with methanol, and drying at 60°C for 12h to obtain modified carbon nanotubes;
[0061] (3) N,N-dimethylformamide and acetone were mixed evenly, polyvinylidene fluoride-hexafluoropropylene copolymer was added and mixed evenly, and modified carbon nanotubes and olefinic silica were added, wherein the mass ratio of N,N-dimethylformamide, acetone, polyvinylidene fluoride-hexafluoropropylene copolymer, modified carbon nanotubes and olefinic silica was 400:100:100:11:4. After stirring and mixing for 4 hours, the mixture was allowed to stand for degassing to obtain a spinning solution, and the spinning solution was added to a spinning machine for electrospinning to form fibers, which were deposited on a polyester mesh substrate. During the electrospinning process, the distance between the needle and the receiving roller was 14 cm, the spinning voltage was 17 kV, the spinning time was 16 h, and the propulsion speed of the spinning solution was 1.4 mL / h to obtain a composite hydrophobic membrane.
[0062] Comparative Example 3
[0063] A method for preparing a composite hydrophobic membrane comprises the following steps:
[0064] N,N-dimethylformamide and acetone are mixed evenly, polyvinylidene fluoride-hexafluoropropylene copolymer is added and mixed evenly, hydroxyl multi-walled carbon nanotubes, perfluorooctyl ethyl acrylate and nano-silica are added, wherein the mass ratio of N,N-dimethylformamide, acetone, polyvinylidene fluoride-hexafluoropropylene copolymer, hydroxyl multi-walled carbon nanotubes, perfluorooctyl ethyl acrylate and nano-silica is 400:100:100:1.8:12.5:0.7, after stirring and mixing for 4 hours, the mixture is allowed to stand for degassing to obtain a spinning solution, and the spinning solution is added to a spinning machine for electrospinning to form fibers, which are deposited on a polyester mesh base lining. During the electrospinning process, the distance between the needle and the receiving roller is 14 cm, the spinning voltage is 17 kV, the spinning time is 16 hours, and the propulsion speed of the spinning solution is 1.4 mL / h to obtain a composite hydrophobic membrane.
[0065] Nano-silicon dioxide used in the examples and comparative examples of the present invention was purchased from Jiangsu Lianyungang Pengrui Chemical Co., Ltd., with a particle size of 15 nm; hydroxylated multi-walled carbon nanotubes were purchased from Shanghai MacLean Technology Biochemical Co., Ltd., with a particle size of 10-20 nm; perfluorooctyl ethyl acrylate CAS No. 27905-45-9, molecular formula C 13 H7F 17 O2; the mesh size of the polyester mesh is 75 μm, the thickness is 82 ± 1 μm, and the density is 40.9 ± 0.5 g / m 2 ; Other undisclosed raw materials and reagents are commercially available.
[0066] The composite hydrophobic membranes in Examples 1-4 and Comparative Examples 1-3 were used as samples with a size of 10 cm×10 cm for performance tests. The relevant performance tests are as follows:
[0067] Contact angle test: Take a sample and fix it with a clamp and place it horizontally on the sample stage. The volume of the water droplet is set to 2.0 μL. Slowly move the sample stage until the membrane surface contacts the water droplet and then move it away. Use a contact angle meter to measure the contact angle of the membrane surface.
[0068] The above test results are shown in Table 1:
[0069]
[0070] As can be seen from the test results in Table 1, the composite hydrophobic membrane of the present invention has excellent hydrophobic properties. Comparative Example 1 uses modified carbon nanotubes, perfluorooctyl ethyl acrylate, and olefinic silica to replace the modified composite material, and the contact angle becomes smaller and the hydrophobic property is reduced. Comparative Example 2 does not add perfluorooctyl ethyl acrylate, and adds modified carbon nanotubes and olefinic silica to replace the modified composite material. The contact angle is 101.2°, and the hydrophobic property is greatly reduced. Comparative Example 3 directly adds hydroxyl multi-walled carbon nanotubes, perfluorooctyl ethyl acrylate, and nano-silica, and the dispersibility and compatibility are greatly reduced, and the contact angle is 119.1°.
Claims
1. A method for preparing a multifunctional composite hydrophobic membrane, characterized in that: The steps include: Step 1, ultrasonically dispersing nano-silica into an ethanol solution, adding γ-methacryloxypropyltrimethoxysilane after uniform dispersion, adjusting the pH to 4 with a hydrochloric acid solution, stirring and mixing, reacting, and after the reaction is completed, filtering, washing, and drying to obtain olefinated silica; Step 2, ultrasonically dispersing hydroxyl multi-walled carbon nanotubes in tetrahydrofuran, adding triethylamine after uniform dispersion, adding 2-bromoisobutyl bromide in a nitrogen atmosphere, stirring and mixing, reacting, centrifuging, washing, and drying after the reaction is completed to obtain modified carbon nanotubes; Step 3: uniformly mix the modified carbon nanotubes, cuprous chloride, perfluorooctyl ethyl acrylate, olefinated silica, and tetrahydrofuran, add 1,1,4,7,10,10-hexamethyltriethylenetetramine in a nitrogen atmosphere, react, centrifuge, wash, and dry after the reaction to obtain a modified composite material; Step 4: Evenly mix N,N-dimethylformamide and acetone, add polyvinylidene fluoride-hexafluoropropylene copolymer and mix evenly, add modified composite material, stir and mix for 2-5 hours, let stand to degas, and obtain spinning solution, add the spinning solution to the spinning machine for electrostatic spinning to form fibers, and deposit them on the polyester mesh base to obtain a multifunctional composite hydrophobic membrane.
2. The method for preparing the multifunctional composite hydrophobic membrane according to claim 1, characterized in that: In the step 1, the mass ratio of the nano-silica, the ethanol solution, and γ-methacryloxypropyltrimethoxysilane is 100:1800-2100:18-35.
3. The method for preparing the multifunctional composite hydrophobic membrane according to claim 1, characterized in that: The reaction temperature in step 1 is 65-75° C., and the reaction time is 4-6 hours.
4. The method for preparing a multifunctional composite hydrophobic membrane according to claim 1, characterized in that: In the step 2, the mass ratio of the hydroxyl multi-walled carbon nanotubes, tetrahydrofuran, triethylamine, and 2-bromoisobutyl bromide is 100:4500-5000:152-180:135-175.
5. The method for preparing the multifunctional composite hydrophobic membrane according to claim 1, characterized in that: During the reaction process in step 2, the reaction is first performed at 0° C. for 4 hours, and then at 25° C. for 36-48 hours.
6. The method for preparing the multifunctional composite hydrophobic membrane according to claim 1, characterized in that: In the step 3, the mass ratio of the modified carbon nanotubes, cuprous chloride, perfluorooctyl ethyl acrylate, olefinated silica, tetrahydrofuran, and 1,1,4,7,10,10-hexamethyltriethylenetetramine is 100:55-65:680-720:25-42:6500-8000:300-350.
7. The method for preparing the multifunctional composite hydrophobic membrane according to claim 1, characterized in that: The reaction temperature in step 3 is 65-75° C., and the reaction time is 48-54 h.
8. The method for preparing a multifunctional composite hydrophobic membrane according to claim 1, characterized in that: In the step 4, the mass ratio of the N,N-dimethylformamide, acetone, polyvinylidene fluoride-hexafluoropropylene copolymer, and the modified composite material is 360-420:90-105:100:5-18.
9. The method for preparing the multifunctional composite hydrophobic membrane according to claim 1, characterized in that: During the electrospinning process in step 4, the distance between the needle and the receiving roller is 12-18 cm, the spinning voltage is 15-18 kV, the spinning time is 12-18 h, and the propulsion speed of the spinning solution is 1.2-1.5 mL / h.
10. A multifunctional composite hydrophobic membrane prepared by the method for preparing a multifunctional composite hydrophobic membrane according to any one of claims 1 to 9.
Citation Information
Patent Citations
Super-hydrophobic polypropylene film and preparation method thereof
CN101531764A
Preparation method of electrostatic spinning hydrophobic nanofiber porous membrane for membrane distillation
CN103263856A
High molecular hydrophobic film and preparation thereof
CN101274991A
Preparation method and application of super-hydrophobic membrane
CN105413488A